PKM Edukasi dan PHBS Pencegahan Cacingan Anak Usia Sekolah sebagai Upaya Menanggulangi Stunting di Kualin NTT - Buntoro, Ika Febianti; Handoyo, Nicholas Edwin; Koamesah, Sangguana Marthen Jacobus; Folamauk, Conrad L. H.; Nurina, Rr.Listyawati; Muntasir, Muntasir (Penerbit Goodwood, 2025)
Purpose: This community service aims to provide educational interventions and knowledge about the importance of preventing worms, instilling good and correct PHBS behavior of washing hands in school-age children, checking the health of nails, hands, skin, and body weight, providing posters for preventing worms and air storage facilities for washing hands. Methodology: The activity consisted of three stages: preparation, implementation, and evaluation. The preparation stage involved site observation, communication with Taus Elementary School, obtaining permits, and providing initial information. Results: The results of this service showed positive results, as many as 52 Taus Elementary School children knew and carried out worm prevention by applying good information using the worm prevention pocketbook, the students were able to carry out demonstrations and practice active participation in carrying out PHBS washing their hands, had carried out health checks. Conclusions: Educational interventions such as lectures and PHBS practices can have a positive impact in increasing health awareness among students. A total of 52 students have the security and knowledge to prevent helminthiasis as one of the causes of stunting with the application of helminthiasis prevention pocket book. Limitations: This activity only reaches 1 Taos elementary school, Oni village, Kualin TTS sub-district, NTT. Contribution: This service is beneficial for schools and the community, maintaining health will endanger worms and increase PHBS hand washing for students and schools to become pilot centers for personal and community hygiene.